Overwinter survival of crustacean diapausing cysts: Brine shrimp (Artemia franciscana) in Great Salt Lake, Utah. (30th May 2019) - Belovsky, Gary E.; Perschon, Clay; Larson, Chad; Mellison, Chad; Slade, Jennifer; Mahon, Heidi; Appiah‐Madson, Hannah; Luft, John; Mosley, Ryan; Neill, John; Stone, Kyle; Kijowski, Ashley; et al.
Abstract: Survivability of diapausing (cryptobiotic) life stages over time in nature, beyond maximum observed time for viability, is not well understood. Because these life stages are an adaptation to overcome harsh conditions, survivability over time is assumed to be high. Brine shrimp ( Artemia franciscana ) diapausing eggs (cysts) permit overwinter survival to initiate the population each spring. An experiment was designed to examine overwinter survival of brine shrimp cysts for 17 yr in Great Salt Lake (Utah, U.S.A.). Initial hatchability entering the winter (17.8–78.8%) and overwinter survivability (9.9–65.9%) of cysts varied dramatically among years. Better maternal nutrition increased initial hatchability. Overwinter survival of cysts decreased in part because some cysts hatch when it is too cold for the hatchlings to feed (0.8–39.4% among years), so they starve. However, overwinter cyst survival decreases the most with warmer waters in winter, and with better maternal nutrition, as both factors lead to diapause being easier to break. Annual variation in initial hatchability and survival is shown to be important to Great Salt Lake brine shrimp populations. Therefore, cryptobiotic life‐stage ecology needs to be better understood, as these life stages may have highly variable hatchability and survivability with normal environmental stresses.